ROOTS OF DESIRE: COMPARING TRAJECTORIES OF LESBIAN IDENTITY IN CONTEMPORARY INDONESIAN AND ENGLISH PROSE - Tira Mariana (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
This comparative study explores the multifaceted trajectories of lesbian identity formation—or “becoming”—in 13 selected contemporary Indonesian and English short stories. By synthesizing narratives sourced from grassroots and digital literary platforms, this research proposes a six-point typology of the “roots” of lesbian desire: conscious choice, spontaneous desire, long-term interaction, early environmental exposure, sexual exploration, and responses to marital trauma. Drawing on Judith Butler’s theory of performativity and Adrienne Rich’s concept of the lesbian continuum, the study critically deconstructs essentialist myths of sexuality. The findings reveal a clear cultural divergence: Indonesian narratives frequently frame lesbian becoming as a strategic and agentic choice to resist state-sponsored heteronormativity and “State Ibuism,” whereas English narratives tend to emphasize the fluid, visceral, and spontaneous nature of desire. Ultimately, the study demonstrates that lesbian becoming functions as a radical reclamation of female agency and as a literary sanctuary from patriarchal failure across both traditions.